FRI0406 Seven-year follow-up of autologous hematopoietic stem cell transplantation for severe systemic sclerosis. (23rd January 2014) - Tsukamoto, H.; Horiuchi, T.; Miyamoto, T.; Niiro, H.; Arinobu, Y.; Akahoshi, M.; Ayano, M.; Tanaka, A.; Ueda, N.; Akashi, K.
Abstract : Background: Autologous stem cell transplantation for international scleroderma (ASTIS) trial demonstrated that autologous hematopoietic stem cell transplantation (auto-HSCT) is more effective than conventional intravenous cyclophosphamide in the treatment of severe systemic sclerosis (SSc). However, there is paucity of the study showing the long-term efficacy of auto-HSCT for severe SSc. Objectives: The aim of this study is to investigate seven-year follow-up results of auto-HSCT for severe SSc. Methods: Nineteen patients (4 male and 15 female) with severe SSc were enrolled. Peripheral blood stem cells (PBSCs) were mobilized with cyclophosphamide (CY, 4 g/m 2 ) and G-CSF. After collecting PBSCs more than 2x 10 6 CD34+cells/kg by apheresis, CD34+ cells were immunologically selected in 11 patients. All of the patients were treated with high-dose CY (200 mg/kg) and received CD34-selected (n=11; a group with CD34-selection) or unmanipulated (n=8; a group without CD34-selection) auto-HSCT. Immune reconstitution was evaluated serially by analyzing lymphocyte subpopulations for 36 months after HSCT. Results: There was no treatment-related mortality. As toxicity, there were a variety of post-transplant infections such as adenoviral hemorrhagic cystitis, herpes zoster and cytomegaloviral antigenemia. Sclerosis of the skin was markedly improved in all of the patients within 6 months and the improvement was sustained for 84 months after auto-HSCT. Vital capacity was significantly increased at 48 and 60 months after HSCT and KL-6, a marker for interstitial pneumonia (IP), was significantly decreased in patients with IP during 12-84 months after HSCT. A titer of anti-Scl-70 was significantly decreased during 1-84 months after HSCT. Five and seven years after auto-HSCT, the overall survival was 89 and 78%, and the progression-free survival was 65 and 57%, respectively. Interestingly, the reduction of the skin scores was significantly greater and viral infections were more frequent in the patients with CD34-selection than those without. Effect of auto-HSCT on interstitial pneumonia, and the recovery of lymphocyte subpopulations after auto-HSCT were not significantly different between two groups. Conclusions: Auto-HSCT was effective in the treatment of SSc and the effect was sustained for 7 years. References: Tsukamoto H, Nagafuji K, Horiuchi T, et al. A Phase I-II Trial of Autologous Peripheral Blood Stem Cell Transplantation in the Treatment of Refractory Autoimmune Disease. Ann Rheum Dis. 65: 508-14, 2006. Tsukamoto H, Nagafuji K, Horiuchi T, et al. Analysis of immune reconstitution after autologous CD34+ stem/progenitor cell transplantation for systemic sclerosis: predominant reconstitution of Th1 CD4+ T cells. Rheumatology 2011; 50: 944-52. Disclosure of Interest: None Declared